Apparent Similarity of Mechanisms of Platelet Adhesion and Aggregation - Mason, R. G.; Read, M. S.; Saba, S. R.; Shekmek, R. W. (Thrombosis and Haemostasis, 1972)
A correlation between effects of a series of compounds on platelet adhesion, aggregation, and retraction of the clot, and their effects on platelet electrophoretic mobility, ecto-ATPase activities, and AChE activity has been sought. Compounds which inhibited aggregation induced by ADP or epinephrine also inhibited platelet adhesion to glass. Six compounds which inhibited adhesion and aggregation did not inhibit clot retraction. The data suggest that the effect of thrombin on platelet electrophoretic mobility and ecto-ATPase activities may have less influence on platelet function than was formerly believed. However, the effects of test compounds on platelet AChE activity suggest that this enzyme may play a role in aggregation and adhesion. Platelet adhesion and aggregation may operate by similar mechanisms.